Estimation of corrugated cardboard strength with a new tensile or shear test method - Norfariza, Ab. Wahab (2012)
The corrugated cardboard is widely used in manufacturing industries as a packaging and transportation material. Faculty of corrugated cardboard is depended on the fragility, weight, thickness, toughness and so on. The strength of corrugated cardboard changed with the fabrication process, used atmosphere and variety of loading patterns. On the machining process of corrugated cardboard box, the cutting and ruling technology is very important factor. The effects of these factors on the strength of corrugated cardboard have not yet enough been identified. In general, the corrugated cardboard was composed with three layer of paperboard. One is outside liner and inside liner and the other is corrugated medium. The top of corrugated medium is bonded with glue on outside or inside layer surface. The bonded space was decided by company standard. The evolutional method of bonding strength had not been established. The development of new simple method has been needed. In this research, to establish the evaluation method of strength of corrugated cardboard material, new practical tensile test and shear test, considering the glue bonding strength, was proposed and the factory of these test method was investigated. In current studies, it was too hard to evaluate the reproductive tensile and shear strength of corrugated cardboard, because of fabrication method of the cut specimen and the deformation of chuck position. On the shear test, as the direction of parallel chuck changed during loading process, the specimen was rotated. In this research, the new developed method of tensile and shear was accomplished, the reproduced strength could be obtained. The fatigue test was tried on the shear test to investigate the effect of thickness of specimen.